Validation of the mobile serious game application Touch Surgery for cognitive training and assessment of laparoscopic cholecystectomy - Kowalewski, Karl-Friedrich; Hendrie, Jonathan D.; Schmidt, Mona Wanda; Proctor, Tanja; Paul, Sai; Garrow, Carly R.; Kenngott, Hannes Götz; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2017)
BackgroundTouch Surgery™ (TS) is a serious gaming application for cognitive task simulation and rehearsal of key steps in surgical procedures. The aim was to establish face, content, and construct validity of TS for laparoscopic cholecystectomy (LC). Furthermore, learning curves with TS and a virtual reality (VR) trainer were compared in a randomized trial.MethodsThe performance of medical students and general surgeons was compared for all three modules of LC in TS to establish construct validity. Questionnaires assessed face and content validity. For analysis of learning curves, students were randomized to train on VR or TS first, and then switched to the other training modality. Performance data were recorded.Results54 Surgeons and 51 medical students completed the validation study. Surgeons outperformed students with TS: patient preparation (students = 45.0 ± 19.1%; surgeons = 57.3 ± 15.2%; p < 0.001), access and laparoscopy (students = 70.2 ± 10.9%; surgeons = 75.9 ± 9.7%; p = 0.008) and LC (students = 69.8 ± 12.4%; surgeons = 77.7 ± 9.6%; p < 0.001). Both groups agreed that TS was a highly useful and realistic application. 46 students were randomized for learning curve analysis. It took them 2-4 attempts to reach a 100% score with TS. Training with TS first did not improve students’ performance on the VR trainer; however, students who trained with VR first scored significantly higher in module 3 of TS.ConclusionTS is an accepted serious gaming application for learning cognitive aspects of LC with established construct, face, and content validity. There appeared to be a synergy between TS and the VR trainer. Therefore, the two training modalities should accompany one another in a multimodal training approach to laparoscopy.